The nutritional and sensory quality of seafood in a changing climate. (April 2022) - Shalders, Tanika C.; Champion, Curtis; Coleman, Melinda A.; Benkendorff, Kirsten
Abstract: Climate change is impacting living marine resources, whilst concomitantly, global reliance on seafood as a source of nutrition is increasing. Here we review an emerging research frontier, identifying significant impacts of climate-driven environmental change on the nutritional and sensory quality of seafood, and implications for human health. We highlight that changing ocean temperature, pH and salinity can lead to reductions in seafood macro and micronutrients, including essential nutrients such as protein and lipids. However, the nutritional quality of seafood appears to be more resilient in taxa that inhabit naturally variable environments such as estuaries and shallow near-coastal habitats. We develop criteria for assessing confidence in categorising the nutritional quality of seafood as vulnerable or resilient to climate change. The application of this criteria to a subset of seafood nutritional studies demonstrates confidence levels are generally low and could be improved by more realistic experimental designs and research collaboration. We highlight knowledge gaps to guide future research in this emerging field. Graphical abstract: Image 1 Highlights: Research assessing the impacts of climate change on the nutritional quality of seafood and effects on human health is rapidly increasing. Climate change can lead to reductions in seafood macro and micronutrients. The effects of environmental change on seafood nutritional and sensory quality is species-specific. We develop a framework for evaluating the confidence in assessments of species nutritional quality to climate-driven environmental change.